Chicken soup for the soul : say goodbye to stress : manage your problems, big and small, every day - Brown, Jeff, 1969-; Neporent, Liz (Cos Cob, CT : Chicken Soup for the Soul Health, 2012)
Collects stories about reducing and managing stress associated with work, home, and finances, and includes medical advice.
Keywords: Stress management -- Popular works; Stress management -- Anecdotes; Stress management; Stress management -- Anecdotes